Analysis of bioactive compounds in cinnamon leaves and preparation of nanoemulsion and byproducts for improving Parkinson’s disease in rats - Wang, Yi Chun; Wang, Vinchi; Chen, Bing Huei (Frontiers in Nutrition, 2023)
Cinnamomum osmophloeum Kanehira (C. osmophloeum), a broad-leaved tree species of Taiwan, contains phenolic acids, flavonoids, and phenylpropanoids such as cinnamaldehyde and cinnamic acid in leaves. Many reports have shown that the cinnamon leaf extract possesses anti-inflammatory, hypoglycemic, hypolipidemic and neuroprotective functions. This study aims to analyze bioactive compounds in C. osmophloeum (cinnamon leaves) by UPLC-MS/MS and prepare hydrosol, cinnamon leaf extract and cinnamon leaf nanoemulsion for comparison in improving Parkinson's disease (PD) in rats. An extraction solvent of 80% ethanol was found to be the most optimal with a high yield of 15 bioactive compounds being obtained following UPLC analysis. A triple quadrupole tandem mass spectrometer with electrospray ionization mode was used for identification and quantitation, with cinnamaldehyde present at the highest amount (17985.2 µg/g). The cinnamon leaf nanoemulsion was successfully prepared with a suitable proportion of cinnamon leaf extract, soybean oil, lecithin, Tween 80 and deionized water, with the mean particle size, zeta potential, polydispersity index and encapsulation efficiency being 30.1 nm, -43.1 mV, 0.149 and 91.6%, respectively. A high stability of cinnamon leaf nanoemulsion was shown over a 90-day storage period at 4℃ and heating at 100℃ for 2 h. Animal experiments revealed that the treatments of cinnamon leaf extract, nanoemulsion and hydrosol increased the dopamine contents from 17.08% to 49.39% and tyrosine hydroxylase levels from 17.07% to 25.59%, while reduced the 𝛼 -synuclein levels from 17.56% to 15.95% in the striatum of rats. Additionally, in the midbrain of rats, an elevation of activities of superoxide dismutase (6.69-16.82%), catalase (8.56-16.94%), and glutathione peroxidase (2.09-16.94%) was shown, while the malondialdehyde content declined by 15.47-22.47%. Comparatively, the high-dose nanoemulsion exerted the most pronounced effect in improving PD in rats and may be a promising candidate for the development of health food or botanic drug.